Application of T-pattern detection and analysis in sports research - Jonsson, G. K.; Anguera, M. T.; Sanchez-Algarra, P.; Olivera, C.; Campanico, J.; Castaner, M.; Torrents, C.; Dinusova, M.; Chaverri, J.; Camerino, O.; Magnusson, M. S. (The Open Sports Sciences Journal, 2010)
The following paper introduces a new approach to the analysis of sports and motor skill performance. The approach, known as T-pattern detection, is explained and preliminary data analyses from soccer, boxing, basketball, swimming and motor skill analysis are presented. The data show that specific temporal patterns can be identified within sports performances. The temporal patterns can relate to performance of specific actions (e.g. passes) or movement patterns. Further analysis showed a significant correlation between coaches` ratings` of performance with the number of temporal patterns exhibited by athletes.